Service Quality Improvement for Radio Frequency Spectrum Usage Monitoring at Balai Monitor Class I Surabaya Using SERVQUAL and AHP Methods - Novitasari, Dyah; Ciptomulyono, Udisubakti (Journal Research of Social Science, Economics, and Management, 2025)
Technological advancements have increased quality demands for frequency spectrum monitoring services. Balmon Surabaya, a UPT under Permenkominfo No. 1 of 2022, supervises the radio frequency spectrum in East Java. However, challenges such as declining monitoring results, numerous complaints, and ineffective disturbance handling have emerged. This study evaluates service quality gaps and proposes improvement strategies for radio frequency spectrum monitoring at Balai Monitor Class I Surabaya using integrated SERVQUAL and AHP methodologies. A quantitative survey collected data from 81 non-major user service recipients through structured questionnaires covering five service dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data analysis employed SERVQUAL gap analysis, Importance-Performance Analysis (IPA), and Analytical Hierarchy Process (AHP), integrated via Quality Function Deployment (QFD). Results revealed negative gaps between user perceptions and expectations across all dimensions, notably tangibles (-0.60), responsiveness (-0.60), reliability (-0.56), and assurance (-0.52). IPA identified six critical attributes in Quadrant I needing urgent attention. AHP prioritized these, with “information on disturbance handling timing” receiving the highest weight (41%). The study recommends five priorities for improvement: enhancing digital and interactive service media; strengthening monitoring and maintenance infrastructure; finalizing operational standards for procedures and service times; digitizing complaint systems with automatic progress updates; and visualizing disturbance handling progress on the user dashboard. These findings provide practical guidance to improve public service quality in frequency spectrum management, supporting more effective wireless communication supervision and lowering interference incidents in East Java.